Knowledge Claims on Municipalities in the Swedish Labor Market Policy - Ulmestig, Rickard (Nordic Journal of Working Life Studies, 2024)
Activation is crucial for beating unemployment for those with high thresholds for entering the labor market. The municipalities in Sweden have become an important factor in the activation. However, no formal argument or decisions were ever made to support the inclusion of municipalities in labor market policy. A government report was, however, compiled and sent to different stakeholders for comments. The present study is based on an analysis of the comments, here termed knowledge claims. The analysis shows that there is a low level of interest from different stakeholders except for the municipalities who are burdened with the cost of social assistance when the unemployed do not find work. The municipalities legitimize and reproduce a dual system for labor market policy. The Public Employment Service (PES) prioritizes unemployed persons who have unemployment insurance and a low threshold for entering the labor market, and the others are left to the municipalities to deal with.